Assessment of prion reduction filters in decreasing infectivity of ultracentrifuged 263K scrapie‐infected brain homogenates in "spiked" human blood and red blood cells. Issue 4 (5th August 2013) - Cardone, Franco; Sowemimo‐Coker, Samuel; Abdel‐Haq, Hanin; Sbriccoli, Marco; Graziano, Silvia; Valanzano, Angelina; Berardi, Vito Angelo; Galeno, Roberta; Puopolo, Maria; Pocchiari, Maurizio
<x xml:space="preserve">Abstract</x> Background The safety of red blood cells (RBCs) is of concern because of the occurrence of four transfusion‐transmitted variant Creutzfeldt‐Jakob disease (vCJD) cases in the United Kingdom. The absence of validated screening tests requires the use of procedures to remove prions from blood to minimize the risk of transmission. These procedures must be validated using infectious prions in a form that is as close as possible to one in blood. Study Design and Methods Units of human whole blood (WB) and RBCs were spiked with high‐speed supernatants of 263K scrapie‐infected hamster brain homogenates. Spiked samples were leukoreduced and then passed through prion‐removing filters (Pall Corporation). In another experiment, RBCs from 263K scrapie‐infected hamsters were treated as above, and residual infectivity was measured by bioassay. Results The overall removal of infectivity by the filters from prion‐spiked WB and RBCs was approximately two orders of magnitude. No infectivity was detected in filtered hamster RBCs endogenously infected with scrapie. Conclusion The use of prion‐removing filters may help to reduce the risk of transfusion‐transmitted vCJD. To avoid overestimation of prion removal efficiency in validation studies, it may be more appropriate to use supernates from ultracentrifugation of scrapie‐infected hamster brain homogenate rather than the current standard brain homogenates.